2021
DOI: 10.3390/ijms22094830
|View full text |Cite
|
Sign up to set email alerts
|

The Interference between SARS-CoV-2 and Tyrosine Kinase Receptor Signaling in Cancer

Abstract: Cancer and viruses have a long history that has evolved over many decades. Much information about the interplay between viruses and cell proliferation and metabolism has come from the history of clinical cases of patients infected with virus-induced cancer. In addition, information from viruses used to treat some types of cancer is valuable. Now, since the global coronavirus pandemic erupted almost a year ago, the scientific community has invested countless time and resources to slow down the infection rate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 86 publications
2
23
0
Order By: Relevance
“…Perhaps not surprisingly, the downstream signalling cascades elicited by cytokines systemically increased in severe COVID-19 have been found to crosstalk with pathways involved in cancer 7 and in fact the present authors have shown that increased AKT1 mRNA levels correlated with poor prognosis in several types of cancer. The PI3K pathway is one of the most commonly activated signalling pathways in estrogen receptor-positive breast cancer 8 .…”
supporting
confidence: 48%
“…Perhaps not surprisingly, the downstream signalling cascades elicited by cytokines systemically increased in severe COVID-19 have been found to crosstalk with pathways involved in cancer 7 and in fact the present authors have shown that increased AKT1 mRNA levels correlated with poor prognosis in several types of cancer. The PI3K pathway is one of the most commonly activated signalling pathways in estrogen receptor-positive breast cancer 8 .…”
supporting
confidence: 48%
“…We evaluated the performance of phage mimicry using representatives of major classes of cell surface receptors, which mediate entry of coronaviruses into the host cells: (1) metallopeptidases, including angiotensin-converting enzyme 2 (ACE2) [1,26], and (2) growth factor receptors, including fibroblast growth factor receptor 3 (FGFR3) [35,37,[78][79][80][81].…”
Section: Landscape Phage Librariesmentioning
confidence: 99%
“…The revealed importance of CD147 in virus infection inspired a search for other potential receptors of the SARS-CoV-2 virus using computational methods [106]. A representative member of the GFR family-fibroblast growth factor receptors (FGFRs)are TKRs that play an important role in cell proliferation, migration, differentiation, and carcinogenesis [80], and are also found to be relevant in viral infections, for example, during endocytosis of the adeno-associated virus 2, and can be considered as a reserve receptor for SARS-CoV-2.…”
Section: Alternative Receptors Of Coronaviruses As An "Operational Re...mentioning
confidence: 99%
See 1 more Smart Citation
“…In SARS-CoV-2 pandemic the Growth factor receptors (GFRs) with intrinsic protein kinase activity are in much consideration. GFRs are relevant for the entry of multiple viruses, including coronaviruses, which makes them a central topic of discussion regarding the SARS-CoV-2 pandemic ( Purcaru et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%